Grande empresa, responsabilidade social e democracia - Riscado, Priscila Erminia (2013)
The question that guides this thesis is the following: the adoption of a socially responsible posture combined with accountability resets the position of large enterprise in the current democratic context? The starting point presented in this work is that the company is an actor who distorts the liberal democracy in contemporary capitalism. Numerous studies point to that direction, signaling how the relationship between States and large companies in the current democratic environment is increasingly characterized by dependency of the first in relation to the last, which become fundamental actors for ensuring jobs and funding democratic capitalist societies...